Synthesis of 125I Labeled Estradiol-17β-Hemisuccinate and Its Binding Study to Estrogen Receptors Using Scintillation Proximity Assay Method - Y. Susilo; G. Mondrida; S. Setiyowati; Sutari Sutari; Triningsih Triningsih; W. Lestari; P. Widayati; C.N. Ardiyatno; A. Ariyanto; S. Darwati; L.B.S. Kardono; A. Yanuar (PPIKSN-BATAN, 2012)
Research was carried out to obtain a selective ligand which strongly bind to estrogen receptors through determination of binding affinity of estradiol-17β-hemisuccinate. Selectivity of these compounds for estrogen receptor was studied using Scintillation Proximity Assay (SPA) method. Primary reagents required in the SPA method including radioligand and receptor, the former was obtained by labeling of estradiol-17β-hemisuccinate with 125I, while MCF7 was used as the receptor. The labeling process was performed by indirect method via two-stage reaction. In this procedure, first step was activation of estradiol-17β-hemisuccinate using isobutylchloroformate and tributylamine as a catalist, while labeling of histamine with 125I was carried out using chloramin-T method to produce 125I-histamine. The second stage was conjugation of activated estradiol-17β-hemisuccinate with 125I-histamine. The product of estradiol-17β-hemisuccinate labeled 125I was extracted using toluene. Furtherly, the organic layer was purified by TLC system. Characterization of estradiol-17β-hemisuccinate labeled 125I from this solvent extraction was carried out by determining its radiochemical purity and the result was obtained using paper electrophoresis and TLC were 79.8% and 84.4% respectively. Radiochemical purity could be increased when purification step was repeated using TLC system, the result showed up to 97.8%. Determination of binding affinity by the SPA method was carried out using MCF7 cell lines which express estrogen receptors showed the value of Kd at 7.192 x 10-3 nM and maximum binding at 336.1 nM. This low value of Kd indicated that binding affinity of estradiol-17β-hemisuccinate was high or strongly binds to estrogen receptor.Received: 04 December 2012; Revised: 19 December 2012; Accepted: 21 December 2012